Direct anterior resin composite bridge – a case report - Ongkowijoyo, Cendranata Wibawa; Sukaton, Sukaton; Rosselle, Veronica Regina (Faculty of Dental Medicine Universitas Airlangga, 2021)
Background: Dental hard tissue loss renders a tooth restorable or unrestorable. The treatment ranges from endodontic treatment to dental implant. Sometimes patients in need to restore their oral function and esthetics cannot afford those treatments due to a limited financial capability and time availability. Purpose: This case report presents a minimal invasive, single appointment, quick, and affordable alternative treatment to restore morphology, function, and esthetics. Case: A 40 years old male patient suffered enamel-dentin-pulp fracture on central incisor due to trauma. Eventhough the fracture involves pulp exposure, it remains vital. The tooth lacks sound tooth structure for ferrule effect. The patient wished to retain the tooth. Therefore, initial treatment plan comprised of reestablishing ferrule effect, root canal treatment, endodontic post, and porcelain crown. Nevertheless, due to financial and time constraint, patient refused the suggested treatment plan; thus, direct resin composite bridge was suggested. Case Management: Isolation is followed by calcium hydroxide capping of the exposed pulp. After application of etch and adhesive bonding to tooth 11, 21, and 22, nanohybrid resin composite was layered to fabricate the direct composite bridge, bonded to 11 and 21, with the following layering sequence: 1) palatal; 2) proximal; 3) body; 4) labial. The procedure took 1 hour to restore tooth morphology, function, and esthetics. Upon five years follow-up, the tooth remains asymptomatic. The direct resin composite bridge has been serving well. Conclusion: Direct resin composite bridges can be an affordable, quick, and minimal invasive treatment modality resulting in satisfactory esthetics, function, and longevity.